Bandgap engineering in V-substituted α-Fe2O3 photoelectrodes. (21st August 2019) - Sathe, Ameya; Seki, Munetoshi; Zhou, Hang; Chen, Jia Xin; Tabata, Hitoshi
Abstract: We demonstrated bandgap engineering of iron oxide ( α -Fe2 O3 ), which is one of the most promising photocatalysts for solar water splitting. It was found that V substitution and thermal annealing in air following film deposition efficiently narrow the bandgap of α -Fe2 O3 . The experimental results suggested that the observed decrease in the bandgap energy is due to the effective hybridization of the 3 d t 2g orbitals of V 5+ and Fe 3+ at the conduction band minimum of V-substituted α -Fe2 O3 . Consequently, a significant enhancement in the photocurrent is observed using the Fe1.67 V0.33 O3 -based photoelectrochemical cell over the wavelength range of 500–800 nm.